Relation between expression of hMLH1 and p53 mRNA genes, in the feces of patients with colorectal carcinoma. Cross-sectional study. (January 2022) - Sitepu, Ryanto Karobuana; Natzir, Rosdiana; Warsinggih,; Hatta, Mochammad; Rudiman, Reno; Labeda, Ibrahim; Lusikooy, Ronald E.; Bukhari, Agussalim; Miskad, Upik A.; Bahar, Burhanuddin
Abstract: Colorectal carcinoma (CRC) is one of the main public health problems. The mortality of CRC is about 8%. Early detection of CRC is very important to prevent death because this cancer could be cured through surgery if the diagnosis can be made as early as possible. Therefore screening strategy for early detection of CRC is critical in reducing mortality. Many investigations supporting the detection of CRC have been developed, including the fecal DNA mutation test using advanced cytological techniques. It is capable of assessing colonocytes for the presence of DNA, RNA, and protein as molecular biomarkers of neoplasia in CRC, including p53 and hMLH1. This study implemented observational approach with a cross-sectional study of the feces of patients with CRC regardless of the stage and grade. The purpose of this study was to determine the expression of the hMLH1 and p53 mRNA genes in the feces of 48 patients with CRC from two hospitals in Indonesia, Siloam Hospitals in Cikarang and Dr. Wahidin Sudirohusodo Hospital in Makassar. The results showed that all adenocarcinoma feces samples with various tumor stages and grades had excess mRNA expression (more than twice the normal amount in Fold Change units) for both the hMLH1 and p53 genes. The average expression of the hMLH1 mRNA gene was the highest at stage two and grade one, while the lowest was at stage four and grade three. In contrast, the average p53 mRNA gene expression was the highest at stage four and grade three, while the lowest was at stage two and grade one. The study suggested that there was a relation between and the expression of hMLH1 and p53 mRNA gene. We concluded that while both hMLH1 and p53 genes in patients' feces with CRC were overexpressed, they did not significantly affect the grade of CRC. Highlights: Relation of mRNA expression of hMLH1 and p53 gene in colorectal carcinoma patients feces. mRNA expression in feces colorectal carcinoma by RT-PCR examination. Gene hMLH1 and p53 in feces colorectal carcinoma patients.